Political [personnel] economy: A political economy perspective to explain different forms of human resource management strategies - Werner Nienhüser (Management Revue, 2004)
A political economy approach to explaining the existence of different human resource strategies is developed in this article - in short: a political personnel economy. The starting point is a critical analysis of the abstinence of politics and power and the resulting explanation deficiencies of traditional microeconomic approaches and of the transactions cost theory. The Marxian labour process theories also discussed in this article, while certainly 'political', primarily exhibit problems related to the theory of action as a foundation. A micro-analytical theory of action-based version of a political economy approach is therefore outlined and applied to the explanation of different human resource management strategies.
Keywords: 650; human resource management; strategies; power; political economy; transactions cost theory; microeconomics; politics; Personalmanagement; Strategisches Management; Transaktionskosten; Mikroökonomik